Financial Literacy for Better Access to Finance, Financial Risk Attitude, and Sustainability of MSMEs in Indonesia - Ferli, Ossi (Jurnal Manajemen, 2023)
MSMEs are one of the sectors affected by the Covid-19 Pandemic in Indonesia, where most of them have experienced a decline in income and many have experienced capital difficulties. Based on data, only a few MSMEs in Indonesia receive financing from financial institutions. While based on previous research, financial literacy is an important factor for MSMEs to get access to finance and can improve their business sustainability. This study aims to analyze the direct effect of Financial Literacy on the sustainability of MSMEs, and indirect effect if mediated by Access to Finance and the Financial Risk Attitude for MSMEs in Indonesia. This study used the Path Analysis model, with primary data from online questionnaires obtained by the snowball sampling method on MSME managers/owners, and for data processing with SmartPLS software. The results showed that Financial Literacy affects MSME's Sustainability, Access to Finance, and Financial Risk Attitude. In this study, Financial Literacy has the greatest influence on Access to Finance. However, Access to Finance and Financial Risk Attitude has no effect on Sustainability and has not succeeded in moderating the relationship between Financial Literacy and the Sustainability of MSMEs. It can be seen that MSMEs in Indonesia may still not have a long-term business development plan and are accustomed to managing business finances in a conventional way, where it has not been able to take advantage of external sources of financing and still minimizes